(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Today there are several different methods of innovative educational technologies. If they use wide and different methods to cover the topic in the lessons, the efficiency of the lesson will be high and the increase of students’ interest in the lesson will be ensured. It is intended to increase the effectiveness of education by bringing innovations into the educational process and implementing them.